Predictive value of HLA class II PCR typing for the outcome of mixed lymphocyte reaction - Cukrová, V; Loudová, M; Srámková, I; Dolezalová, L; Vítek, A (Folia biologica, 1998)
The use of HLA-DRB1 and -DQB1 polymerase chain reaction-sequence-specific primer (PCR-SSP) typing at different levels of resolution for MLR prediction was assessed in 54 HLA-A and -B matched donor/recipient unrelated pairs and 89 HLA-A and -B identical siblings. Graft-versus-host (GvH) direction one-way MLR was evaluated unless stated otherwise. The typing of DRB1 alleles satisfactory for MLR prediction in HLA identical siblings (P = 0.0015) does not appear to be sufficient in matched unrelated pairs (P = 0.2407). Using more discriminatory PCR-SSP typing, the disparity in DRB1 allelic subtypes was predominantly found in the category of DRB1 allele compatible, MLR positive unrelated pairs. Besides, DRB1 allelic subtype mismatches were revealed in five of the forty-one DRB1 allele compatible, MLR negative unrelated pairs. More discriminatory typing made the correlation between DRB1 compatibility and MLR negativity extremely significant (P = 0.0001). As for these five exceptional cases, the reciprocal host-versus-graft (HvG) direction MLR was considered, too. This allowed HLA-D disparity to be disclosed in two of them. An uninterpretable result reflecting defective MLR reactivity occurred in one case. Negative reciprocal MLR in the last two DRB1 allelic subtype incompatible pairs is hardly to explain without postulation of MLR silent DRB1 allelic subtype mismatches. An analysis in unrelated pairs showed a role of some DQB1 gene products in the proliferative response too. GvH direction positive MLR was found in two HLA identical siblings among the 89 tested. The DPB1 incompatibility detected in one of them could be a potential cause of proliferative response but MLR reactivity in the other, DPB1 identical, pair cannot be interpreted easily.
Keywords: alely; Nuclear Family; HLA-B Antigens; transplantace kostní dřeně; Humans; HLA-DRB1 řetězec; Predictive Value of Tests; HLA-DQ beta-Chains; nukleární rodina; HLA-A Antigens; Female; Alleles; Tissue Donors; lidé; HLA-DRB1 Chains; HLA-B antigeny; HLA-DR antigeny; HLA-D antigeny; Bone Marrow Transplantation; Lymphocyte Culture Test, Mixed; testování histokompatibility; HLA-DQ beta řetězec; dárci tkání; HLA-DR Antigens; ženské pohlaví; Male; hodnotící studie jako téma; prediktivní hodnota testů; test smíšené lymfocytární kultury; HLA-DQ Antigens; polymerázová řetězová reakce; HLA-DQ antigeny; Polymerase Chain Reaction; Histocompatibility Testing; HLA-A antigeny; HLA-D Antigens; mužské pohlaví; Evaluation Studies as Topic